PERAN MASYARAKAT DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH YANG DEMOKRATIS - I Gusti Ayu Oka Pramitha Dewi; Ida Bagus Wyasa Putra (Kertha Negara : Journal Ilmu Hukum, 2015)
This paper is about the manifestation of the role of the community in the area ofdemocratic governance. The problems that occurred that embodiment of society's rolein the area of democratic governance is not entirely clear set in the rule of law inIndonesia, causing blurring the role of society in local governance to carry out aregional autonomy demokratis. This paper aims to understand and appreciate the roleof the public manifestation in the area of democratic governance. This paper, using themethod of the normative legal research with this kind of approach to the analysis oflegislation. This paper presented a study that in a democracy is a government of thepeople by giving authority to the community through participation embodiment.Democracy means rule system of government from the people. Democracy can foster afeeling of belonging to the community and is responsible for the development inaccordance with the meaning of democracy is government of, by and for the people. Theprocess of implementation of the program and the implementation of democraticdevelopment in the local government which is based on community participationinclude the planning and implementation of programs, dialogue with the public anddecision-making.